Do descendants of families contribute to type 2 diabetes mellitus? - Fatma Nuraisyah; Solikhah Solikhah; Rochana Ruliyandari (International Journal of Public Health Science (IJPHS), 2020)
Diabetes is a public health problem in Indonesia that has been increasing in recent decades. Screening for diabetes was usually identified as pregnant women, adolescents, adults, children, older and obesity, while based on investigation descendent was yet. This cross-sectional study aimed to know the random level blood glucose of family history type 2 diabetes mellitus (T2DM). The target group for screening was people with a family history in one of their descent of T2DM with age >20 years in Kulon Progo, DIY, Indonesia. We conducted a detection of random level blood glucose from a venous blood sample. A high level of blood glucose was diagnosed when random blood glucose reaches ≥200 mg/dl. The participant with high level of blood glucose was 29.0%, while borderline blood glucose (≥110-199 mg/dl) was revealed 38.7% of 15.3% subject indicated with mother history. Descendant screening of family history T2DM is early detected respondent with high glucose level and reduced the severe complication.